PERBANDINGAN BERBAGAI MIKROORGANISME LOKAL (MOL) PADA PROSES PENGOMPOSAN SECARA ANAEROBIK: Comparison of Various Local Microorganisms (MOL) in Anaerobic Composting Process - Kamarullah, Novitasari; Dwi Wahyu Purwiningsih; H, Haikun; Laudo, Karmila; Bano, Efirufini H.; Derlen, Zainy Azhary (Poltekes Kemenkes Tanjungpinang, 2021)
Garbage is solid waste consisting of organic and inorganic substances which are considered useless and must be managed. Composting is a method of converting organic materials into simpler materials using microbial activity. MOL is a group of micro-organisms that function as a